Business Cycle Fluctuations and International Financial Integration - Renatas Kizys; Christian Pierdzioch (Kiel Institute for World Economics (IfW), 2004)
Theoretical research on the determinants of business-cycle fluctuations implies that the degree of international financial integration can have important implications for the propagation of, e.g., macroeconomic policy shocks in an open economy. An important assumption underlying this research is that the degree of financial integration can be taken as exogenously given. Because recent empirical research has demonstrated that financial integration may change over time, we use data for the G7 countries to test how well this assumption fits to the data. We find that one can maintain, as a rule, the assumption that the degree of financial integration is invariant to the determinants of the business-cycle fluctuations. We find, however, a few exceptions from this rule, and we also find that shocks tend to have a highly persistent effect on financial integration.
Keywords: F33; F41; F36; 330; Open economy macroeconomics; Business cycles; Financial integration; Konjunktur; Internationaler Finanzmarkt; Aktienmarkt; Marktintegration; Internationaler Preiszusammenhang; Schätzung; G7-Staaten